Fixture Design and Verification for Component of Bench Vise 125 - Asep Indra Komara ,Dedy Ariefijanto,Muhammad Fadhlan Afif (International Conference on Industrial Revolution for Polytechnic Education, 2020)
The main objective of this paper is to design and verification fixture for POLMAN Bandung bench vise 125 component, which reduces the using of machine tool and improve the product quantity at the lower time. The main components of POLMAN Bandung bench vise are moving jaw and fixed jaw. Machining of these two main components were done by using conventional machine with existing jigs and fixtures. Product quality and quantity do not meet current expectations so that the production process needs to be improved. This can be achieved by replacing conventional machines to CNC machine. Some steps taken to solve this problem are: (1) study the vise component, (2) study and observe the current machining, (3) study MH4BN CNC machine, (4) identifying the operator, (5) identifying requirements and production cost, (6) new design specification, (7) planning the cutting tools, (8) layout alternatives, (9) fixture concept design, (10) fixture design alternatives, (11) fixture verification, (12) fixture draft design, and (13) operation procedure. Based on this study, a fixture that can meet expectations is produced. The fixture can machine four components arranged in four positions which consisting of two moving jaws and two fixed jaws. The fixture’s size are 600x556x565 with 237 kg in weight. loading-unloading can be done at the same time of machining. The fixture is able to withstand machining forces. Contact stability of critical fixture components compared to product tolerance is still within the permissible limits. Machining the two main component of POLMAN bench vise decrease from 11.5 hours to 1.4 hours.